Working with comics textual genre with students with intellectual disabilities - Shimazaki, Elsa Midori; Auada, Viviane Gislaine Caetano; Menegassi, Renilson José [UNESP]; Mori, Nerli Nonato Ribeiro (FapUNIFESP (SciELO), 2018)
School is a social space established for the mediation of scientific concepts that organize and guide society. Among the scientific concepts that should be mediated are those related to the Comics textual genre, which is normally exercised in the classroom and of daily circulation. Thus, this text aims to report, analyze and reflect on the strategies developed for people with intellectual disabilities to appropriate scientific concepts present in the comic books, based on the principle that it is the responsibility of the school to work with the development of scientific concepts, including those related to a specific textual genre of social circulation. It is an action research developed with four students from a public school in the Northwest of Paraná state, Brazil, which incorporates the Youth and Adult Education (called EJA) modality at Elementary and High School level. To reach the proposed objective, in the initial phase of the research, background knowledge of the subjects was identified, which served as support to plan the significant interventions for the group. After the intervention, it was verified that the subjects appropriated the set of scientific concepts that constitute the Comics textual genre and improved the quality of their understanding and interpretation of the Comics and, consequently, their possibilities of social interaction.
O trabalho com o gênero textual história em quadrinhos com alunos que possuem deficiência intelectual
Keywords: Comics; Literacy; Special education; Textual genres; Young people and adults